The Effects of changes in Tariff Rates on Imports: Evidence from Kazakhstan - A. N. Aituar; S. S. Kemelbayeva (Экономика: стратегия и практика, 2022)
This paper is the continuation of the research on the impact of Eurasian Customs Union policies on the economy of Kazakhstan.   The study provides new evidence on the effects of Customs Unions on its members. In particular, this paper investigates the impact of tariff rate changes in Kazakhstan due to the establishment of the Eurasian Economic Union. Kazakhstan joined Eurasian Customs Union in 2010. Then the Eurasian Customs Union became the Eurasian Economic Union in May 2014. Since the establishment of the ECU, Kazakhstan’s trade policy has experienced considerable change. The tariff rates in Kazakhstan with countries outside the ECU almost doubled, with average tariff rates increasing from 6.45 to 12.24 %. This paper uses the dataset on bilateral trade flows between ECU countries and other 195 countries for 20 years from 2000 to 2019. An empirical analysis is performed on a country level, and panel data techniques are used to estimate whether the increase in the tariffs with non-members of CU will lead to trade diversion with suppliers outside the CU. The analysis demonstrated that the increase in tariff rates negatively affected imports to Kazakhstan from non-ECU countries. The effect of tariff increase, using the dynamic gravity model and GMM econometric technique, is estimated to be a 1.8 % decrease in imports if the average external tariff rate of Kazakhstan increases by one percentage point (e. g. from 7 % to 8 %). Due to the increase in tariff rates, the overall estimated reduction of imports of Kazakhstan is 10.66 %.